2017
DOI: 10.1021/acs.analchem.7b02880
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Loaded Nanoporous Ferric Oxide Nanocubes with Peroxidase-Mimicking Activity for Electrocatalytic and Colorimetric Detection of Autoantibody

Abstract: The enzyme-mimicking activity of iron oxide based nanostructures has provided a significant advantage in developing advanced molecular sensors for biomedical and environmental applications. Herein, we introduce the horseradish peroxidase (HRP)-like activity of gold-loaded nanoporous ferric oxide nanocubes (Au-NPFeONC) for the development of a molecular sensor with enhanced electrocatalytic and colorimetric (naked eye) detection of autoantibodies. The results showed that Au-NPFeONC exhibits enhanced peroxidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 51 publications
3
140
0
Order By: Relevance
“…In other report, Masud et al reported the significant enhancement in catalytic properties of porous Fe 2 O 3 nanocubes for TMB oxidation through the loading of Au NPs. This enhancement was attributed to the provision of a larger contact area to promote improved interaction with the positively charged TMB.…”
Section: Functional Applications Of Iron Oxide‐based Nanoarchitecturesmentioning
confidence: 92%
“…In other report, Masud et al reported the significant enhancement in catalytic properties of porous Fe 2 O 3 nanocubes for TMB oxidation through the loading of Au NPs. This enhancement was attributed to the provision of a larger contact area to promote improved interaction with the positively charged TMB.…”
Section: Functional Applications Of Iron Oxide‐based Nanoarchitecturesmentioning
confidence: 92%
“…This reaction has been widely used to design sensitive biosensors for detecting hydrogen peroxide, glucose, cells, and disease‐specific biomolecules ,,,. Recently, we have reported the synthesis and peroxidase mimetic activity of gold‐loaded nanoporous iron oxide materials for colorimetric and electrochemical detection of cancer biomarker, p53 autoantibody . Herein, we have elaborately studied the mechanism involved in the peroxidase mimetics of four different engineered IONF samples and compared their performance to obtain the optimum nanozyme for future biosensing.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the IONF_250 sample exhibited a much higher absorbance compared to the control sample by almost 13‐fold (0.546 versus 0.042) at 652 nm (Figure b). The possible mechanism for IONFs‐induced peroxidase mimetics could be due to the ferric ions (Fe 3+ ) (from IONFs) initiating the oxidation of TMB by generating hydroxyl free radical (⋅OH) from H 2 O 2 following the Fenton reaction, as shown in Equations (i) to (iv) trueFe3++normalH2normalO2FeOOH2++normalH+ trueFeOOH2+Fe2++HO2 trueFe2++normalH2normalO2Fe3++OH-+OH trueOH+TMB(colourless)TMBox(blue) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A peroxidase-mimetic nanomaterials-based sensor was demonstrated recently (Figure 8b) [63]. The recognition element was the antigen attached to the carbon electrode.…”
Section: Sensitive Detection Strategymentioning
confidence: 96%